ANALISIS PENGARUH MOTIVASI, KEMAMPUAN, DIKLAT, DAN KESEMPATAN BERKARIER TERHADAP KINERJA ANGGOTA POLSEK SAWAHAN POLRES MADIUN KOTA - Suyanto Waspo Tondo Wicaksono (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2019)
From the test results obtained on the validity test results are known that all question items have valid. While the reliability test results are known that all items are reliable questions. From the results of multiple regression results obtained all positive coefficient. This shows that each increase in variable X will be followed by an increase in variable Y. In the classical assumption test results obtained that the regression equation has fulfilled the classic assumption that the data are normal, there is no multicollinearity, heteroscedasticity does not occur, and no autocorrelation occurs. On the correlation coefficient correlation value (R) turns out that the correlation is positive. This means that there is a strong unidirectional relationship, where changes in the increase that occur in the independent variable are the motivation variable (X1) ability (X2), training (X3), and career opportunities (X4) followed by an increase in the dependent variable namely performance (Y ) member of the Sawahan City Police Madiun District Police Station. From the results of the study it was found that the X4 variable, namely the experience variable, was the independent variable that predominantly influenced the dependent variable, namely the performance (Y) of the Sawahan District Police Madiun District Police. In testing with the F test and with the t test it is known that the independent variable is the motivational variable (X1) ability (X2), training (X3), and career opportunities (X4) both simultaneously and partially have a significant effect on the dependent variable namely performance (Y ) member of the Sawahan City Police Madiun District Police Station.